SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN BANTUAN SOSIAL DALAM PEMENUHAN KEBUTUHAN LANSIA TERLANTAR DI KOTA BENGKULU - Candra Alexander; Lena Elfianty; Eko Suryana (Smart Education, 2023)
Abstract: Elderly assistance is an assistance program provided by the government through the Social Service for elderly people aged 60 years and over who are in the poor category. However, currently the elderly assistance program is still not optimal because there are obstacles encountered such as limited members and the absence of an electronic data input system so that data collection still uses manual recording on paper making the process of determining elderly assistance takes a long time. Therefore a decision support system was designed to determine the provision of social assistance in fulfilling the needs of abandoned elderly people in the city of Bengkulu using the Promethee method. This decision support system is designed using the PHP Programming Language and MySQL database. The system created can make it easy for the Social Service to determine elderly recipients of social assistance in the city of Bengkulu.Keywords: decision support system; promethee; bengkulu social service Abstrak: Bantuan lansia merupakan program bantuan yang di berikan pemerintah melalui Dinas Sosial untuk kaum lansia umur 60 tahun keatas yang masuk kategori tidak mampu. Namun saat ini program bantuan lansia masih belum maksimal karena ada kendala yang dihadapi seperti terbatasnya anggota dan belum adanya sistem input data elektronik sehingga pendataan masih menggunakan pencatatan manual di kertas membuat proses penentuan bantuan lansia membutuhkan waktu yang lama. Oleh karena itu dirancang sistem pendukung keputusan untuk menentukan pemberian bantuan sosial dalam pemenuhan kebutuhan kepada lansia terlantar di kota Bengkulu menggunakan metode Promethee. Sistem pendukung keputusan ini dirancang menggunakan Bahasa Pemrograman PHP dan database MySQL. Sistem yang dibuat dapat memberikan kemudahan bagi Dinas Sosial untuk menentukan lansia penerima bantuan sosial di kota Bengkulu.Kata kunci: sistem pendukung keputusan; promethee; dinas sosial bengkulu